The Potential of Soursop Seed Extract Annona muricata Linn as a Biopesticide against Aphids Aphis gossypii Glover (Homoptera: Aphididae) on Chilly - Abdullah, Fauziah; Sina, Ibnu (Malaysian Journal of Science, 2003)
Aphids of the fourth instar of Aphis gossypii were subjected to toxicity test against 80,000 ppm, 60,000 ppm, 40,000 ppm, 20,000 ppm, 10,000 ppm, 5,000 ppm, 1,000 ppm of seed extract of Annona muricata. Diathion 1,000 ppm and water were used as control. 59% aphids mortality was reached within 24 hours for the 80,000 ppm concentration whereas 50% mortality occurred only 48 hours after application for the 60,000 ppm concentration. For the 40,000 ppm and 20,000 ppm concentrations, 48% and 52% mortality were reached after 72 hours and 120 hours after application respectively. The ladybird beetle Epilachna indica (Coleoptera: Coccinelidae) exposed to 80,000 ppm and 40,000 ppm response stock extract showed toxic response 48 hours after application while the symbiont ant Oecopylla smaragdina (Hymnoptera: Formicidae) was not affected. This study shows that the extract of Annona muricata seed has potential as a biopesticide against aphid pests of vegetable species in Malaysia.Aphids of the fourth instar of Aphis gossypii were subjected to toxicity test against 80,000 ppm, 60,000 ppm, 40,000 ppm, 20,000 ppm, 10,000 ppm, 5,000 ppm, 1,000 ppm of seed extract of Annona muricata. Diathion 1,000 ppm and water were used as control. 59% aphids mortality was reached within 24 hours for the 80,000 ppm concentration whereas 50% mortality occurred only 48 hours after application for the 60,000 ppm concentration. For the 40,000 ppm and 20,000 ppm concentrations, 48% and 52% mortality were reached after 72 hours and 120 hours after application respectively. The ladybird beetle Epilachna indica (Coleoptera: Coccinelidae) exposed to 80,000 ppm and 40,000 ppm response stock extract showed toxic response 48 hours after application while the symbiont ant Oecopylla smaragdina (Hymnoptera: Formicidae) was not affected. This study shows that the extract of Annona muricata seed has potential as a biopesticide against aphid pests of vegetable species in Malaysia.